2009
DOI: 10.1111/j.1365-2966.2009.15420.x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical assessment of shapes and magnetic field orientations in molecular clouds through polarization observations

Abstract: We present a novel statistical analysis aimed at deriving the intrinsic shapes and magnetic field orientations of molecular clouds using dust emission and polarization observations by the Hertz polarimeter. Our observables are the aspect ratio of the projected plane‐of‐the‐sky cloud image and the angle between the mean direction of the plane‐of‐the‐sky component of the magnetic field and the short axis of the cloud image. To overcome projection effects due to the unknown orientation of the line‐of‐sight, we co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 34 publications
(53 reference statements)
7
45
2
Order By: Relevance
“…FUTURE WORK Along with our work on interpreting the data from individual objects presented here (e.g., the last column of Table 1), we have begun to look for meaningful relationships in the Hertz database as a whole. For example, Tassis et al (2009) have tested models of magnetic cloud support by comparing the mean polarization position angles in each cloud with their observed shapes. Li et al (2009) have compared similar mean cloud position angles with those from optical polarimetry in an effort to investigate the relation between interstellar magnetic fields in dense clouds with those in the diffuse interstellar medium.…”
Section: Resultsmentioning
confidence: 99%
“…FUTURE WORK Along with our work on interpreting the data from individual objects presented here (e.g., the last column of Table 1), we have begun to look for meaningful relationships in the Hertz database as a whole. For example, Tassis et al (2009) have tested models of magnetic cloud support by comparing the mean polarization position angles in each cloud with their observed shapes. Li et al (2009) have compared similar mean cloud position angles with those from optical polarimetry in an effort to investigate the relation between interstellar magnetic fields in dense clouds with those in the diffuse interstellar medium.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the gradient technique can sample multiple scales by increasing the size of the vicinity of pixels used for its calculation (derivative kernel; see Appendix B.1). Previous studies that assign an average orientation of the cloud (Tassis et al 2009;Li et al 2013) are equivalent to studying the relative orientation using a derivative kernel close to the cloud size.…”
Section: Histogram Of Relative Orientationsmentioning
confidence: 99%
“…On the other hand, if the plotted pseudo-vectors correspond to the polarization in a particular pixel, then the illustrated pattern is influenced by small-scale fluctuations that might not be significant in evaluating any trend in relative orientation. Tassis et al (2009) present a statistical study of relative orientation between structures in the intensity and the inferred magnetic field from polarization measured at 350 µm towards 32 Galactic clouds in maps of a few arcminutes in size. Comparing the mean direction of the field to the semi-major axis of each cloud, they find that the field is mostly perpendicular to that axis.…”
Section: Introductionmentioning
confidence: 99%
“…And indeed, observations of polarization in regions of star formation have shown that magnetic fields (B-fields) often are well-ordered on scales from ∼100 pc (Heiles 2000) down to ∼1 pc, which suggests that on large scales B-fields are dynamically important. At smaller scales ambipolar diffusion (e.g., Mestel & Spitzer 1956;Fiedler & Mouschovias 1993;Tassis et al 2009) or turbulent magnetic reconnection diffusion (Lazarian 2005;Leão et al 2013) are thought to allow 19 South Africa SKA Fellow. 20 Hubble Fellow.…”
Section: Introductionmentioning
confidence: 99%